The fight over the global development agenda: How the West tries to marginalise UNCTAD - Robert H. Wade (Intereconomics, 2012)
The UN Conference on Trade and Development (UNCTAD) has a long history of intellectual independence. This article details how Western countries tried to marginalise the organisation and its work - which is often critical of Western powers - during the 2012 UNCTAD conference. While developing countries were able to mobilise and partially beat back these attempts for now, the organisation's ability to contribute to global macroeconomics remains under threat.
Keywords: 330; Entwicklungsorganisation; Außenwirtschaftspolitik; Industriestaaten; Entwicklungshilfe; Welt